Ácido tânico como agente biomodificador de dentina - Mendes, Talita Arrais Daniel (2019)
Introduction: The use of different polyphenols in the increase of the mechanical properties of dentin collagen has been widely used, thus, tannic acid being a polyphenol with very pronounced biological proprieties. Objective: to evaluate the biomodifying potential of tannic acid (AT) in different concentrations in dentin collagen. Methods: the factors under investigation were modulus of elasticity, measured by a three-point bending test (n = 10), and mass variation (n = 10), measured by means of a precision scale, being the following substances evaluated: tannic acid (0.1, 1 and 10%), proanthocyanidin (6.5%) and distilled water (control). Results: As for the modulus of elasticity, the groups treated with tannic acid presented statistically higher values (p <0.05) in relation to the other groups, and no differences were observed between the different concentrations. For the values of mass variation, the groups that were immersed in biomodifiers showed statistically (p <0.05) values higher than the control group. Conclusion: tannic acid presents as a potential biomodifying agent of dentin collagen, regardless of the concentration used, increasing its modulus of elasticity and generating a mass gain after one hour of immersion.